THE INFLUENCE OF HUMAN RELATIONS AGAINST SPIRIT WORK EMPLOYEES OF PT. VICTORY INTERNASIONAL FUTURE MAKASSAR BRANCH - Andi Dewi Putriani; Mahlia Muis; Andi Reni (Paulus Journal of Accounting (PJA), 2023)
The Influence of Human Relations Against Spirit Work Employees of PT Victory International Futures Makassar Branch Study This aim is to know how to influence human relations through spirit work for employee PT. Victory International Futures Makassar Branch. Human relations (human-to-human relationships) are a necessary condition for success. Good communication between individuals and communication in companies Harmonious relations between employees make working situations and conditions conducive; this is a manifestation of the implementation of human relations, which will ultimately lead to morale for all parties. Type of research used: This is done through descriptive and quantitative research. Data collection was carried out with a share questionnaire distributed to 33 respondents at PT. Victory International Futures Makassar Branch, with the testing of hypotheses using simple linear regression. Based on the results of the simple regression analysis, the mark coefficient for human relations is -1019 to show that Human Relations (X) has a negative and significant effect on spirit work (Y) at the PT. Victory International Futures Makassar branch because that hypothesis was declared "rejected ".